Taxonomy, Biodiversity, and Ecology of Parasites of Aquatic Organisms: A Special Issue - Philippe Vieira Alves; José Luis Luque (Diversity, 2023)
Parasitism is ubiquitous and one of the most successful lifestyles on Earth, with more than 200 independent transitions from non-parasitic ancestors considered only in the kingdom Animalia [...]